A highlander Christmas - Chapman, Janet (New York : Pocket Star Books, 2009)
Camry MacKeage left her job as a NASA physicist for the small-town life of a dog-sitter. Her rival at NASA, Luke Pascal, tries to tempt Camry home for the family's annual winter solstice celebration. But Luke is hiding his own secret, and he'll need a little bit of magic to earn Camry's trust.
Keywords: Man-woman relationships -- Fiction; Small cities -- Fiction; Maine -- Fiction; Christmas stories; Love stories